2013
DOI: 10.1371/journal.pone.0056719
|View full text |Cite
|
Sign up to set email alerts
|

Mice Deficient in the Respiratory Chain Gene Cox6a2 Are Protected against High-Fat Diet-Induced Obesity and Insulin Resistance

Abstract: Oxidative phosphorylation in mitochondria is responsible for 90% of ATP synthesis in most cells. This essential housekeeping function is mediated by nuclear and mitochondrial genes encoding subunits of complex I to V of the respiratory chain. Although complex IV is the best studied of these complexes, the exact function of the striated muscle-specific subunit COX6A2 is still poorly understood. In this study, we show that Cox6a2-deficient mice are protected against high-fat diet-induced obesity, insulin resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 79 publications
4
62
0
Order By: Relevance
“…5 and 6). These findings are interesting since in numerous mouse models (6,41,58,60), DIO resistance is accompanied by improved glucose homeostasis. Compared with controls, IL-15R␣ Ϫ/Ϫ mice had hyperglycemia, hyperinsulinemia, and higher insulin secretion during GTT, independently of age (Figs.…”
Section: Discussionmentioning
confidence: 91%
“…5 and 6). These findings are interesting since in numerous mouse models (6,41,58,60), DIO resistance is accompanied by improved glucose homeostasis. Compared with controls, IL-15R␣ Ϫ/Ϫ mice had hyperglycemia, hyperinsulinemia, and higher insulin secretion during GTT, independently of age (Figs.…”
Section: Discussionmentioning
confidence: 91%
“…3C). COX6A2 is a subunit of respiratory cytochrome c oxidase (complex IV) expressed in striated muscle and shown to play a role in respiratory uncoupling in muscle (35). Studies in yeast demonstrated that COX6 expression is up-regulated by heme (36), thus the increase in Cox6a2 expression in Flvcr -deleted thymocytes may result from increased heme levels.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, modification of mitochondrial dynamics has been highlighted as a potential mechanism in muscle IR, as muscle from obese subjects and from T2DM patients has shown reduced expression of mitofusin-2 (Mfn2) [23], and amelioration of insulin sensitivity by bariatric surgery has been associated with increased Mfn2 expression in muscle [24]. Nevertheless, other studies performed in mice with genetic ablation of different components of mitochondria have minimalized the role of mitochondrial dysfunction in muscle IR [25][26][27][28][29], and further interventional studies have also supported the controversy [30,31], questioning the causal implication of mitochondria in alterations of insulin signalling. Consistent with this, we have demonstrated that mitochondrial dysfunction in T2DM is not an early abnormality playing a causal role in the development of the disorder, but rather a complication of oxidative stress associated with hyperglycaemia and hyperlipidaemia-at least in diet-induced diabetic mice [32].…”
Section: Mitochondrial Dysfunction and Skeletal Muscle Insulin Resistmentioning
confidence: 99%